DURABILITY CHARACTERISTICS OF MICROBIAL INDUCED CALCITE PRECIPITATE/CEMENT STABILIZED LATERITE BLOCKS - Abdullahi, S.; Amartey, Bilkisu Hassan Sada; Kaura, J. M.; Amartey, Y. D. (FUDMA JOURNAL OF SCIENCES, 2024)
This study investigates the strength and durability characteristics of molded laterite blocks stabilized with microbial-induced calcite precipitate (MICP) bacteria namely Bacillus coagulans (B.coagulans) and cement. The properties checked includes the water absorption and wet compressive strength of the laterite blocks tested at different curing ages of 7-, 14-, 21-, and 28 days by examining the impact of B.coagulans calcite precipitate, cement, and the combined effects of both on these properties. The B.coagulans bacteria having a 3g/l nutrient broth content served as the bio-calcination agent, while ordinary Portland cement acted as the stabilizer, The B. coagulans concentrations were varied at 0, 1.5E+08, 6.0E+08, 1.2E+09, 1.8E+09 and 2.4E+09 cell/ml suspension densities using the McFarland standards. From results obtained the water absorption properties shows improvement, decreasing from 32% for un-stabilized soil to optimal values of 15%, 9%, and 6% for MICP-stabilized, cement-stabilized, and MICP 5% cement-stabilized laterite blocks, respectively, at 28 days of curing. The wet compressive strength of un-stabilized soil ranges from 0.5 to 1.0 N/mm2 for curing periods 7 to 28 days respectively which is lower than for the stabilized laterite blocks which were 1.99 N/mm2 for 1.80E09 cell/ml B.coagulans suspension density and 3.7 N/mm2 for 5% cement stabilized laterite blocks at 2.4E09 cell/ml B. coagulans suspension density after 28 days curing.  Results obtained showed that the stabilized laterite blocks outperform the unstabilized blocks and therefore the cement-MICP combination used gave positive outcomes in stabilization of laterite blocks with a minimal percentage of 5% cement-stabilized MICP for sustainable building applications.